2020
DOI: 10.3354/esr01022
|View full text |Cite
|
Sign up to set email alerts
|

Giraffe translocation population viability analysis

Abstract: Most populations of giraffes have declined in recent decades, leading to the recent IUCN decision to upgrade the species to Vulnerable status, and some subspecies to Endangered. Translocations have been used as a conservation tool to re-introduce giraffes to previously occupied areas or establish new populations, but guidelines for founding populations are lacking. To provide general guidelines for translocation projects regarding feasibility, we simulated various scenarios of translocated giraffe populations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, PVA provided a valuable framework for evaluating the impact of management actions on an endangered species. The use of PVA to evaluate conservation actions has been mainly focused on mammals and birds and occasionally on lizards (Kacoliris et al, 2019; Lee et al, 2020; García‐Antón & Traba, 2021). However, assessment of conservation actions through PVA is less widespread among aquatic species, including amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PVA provided a valuable framework for evaluating the impact of management actions on an endangered species. The use of PVA to evaluate conservation actions has been mainly focused on mammals and birds and occasionally on lizards (Kacoliris et al, 2019; Lee et al, 2020; García‐Antón & Traba, 2021). However, assessment of conservation actions through PVA is less widespread among aquatic species, including amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…PVA can predict translocation outcomes and should be central to any translocation planning and decision‐making process (Dimond & Armstrong, ; IUCN, ). PVA simulations have shown that in order to establish a long‐term (100 years), genetically viable population of giraffes, a minimum of 30 females is required for the founding population (Lee et al, ). This is a substantially higher figure than is usually moved in practice (Chege, ; Muller, ).…”
Section: Initial Planning and Justificationmentioning
confidence: 99%
“…Given the current uncertainty over giraffe taxonomy (Bercovitch et al, ; Fennessy et al, ), long‐term isolation of some populations (e.g . G. c. thornicrofti ), and deleterious effects of inbreeding depression (Lackey, ; Lee et al, ), genetic factors should be considered in giraffe translocation events. Guidance regarding taxonomic classification and distribution of giraffes is available from the IUCN SSC Giraffe and Okapi Specialist Group (http://www.giraffidsg.org), and general genetic diversity advice is available from population biologists experienced with small‐population genetics.…”
Section: Selecting Individuals For Translocationmentioning
confidence: 99%
See 2 more Smart Citations